Teilnehmerkreis der Basler Lesegesellschaft 1825-1915. Eine Kollektivbiographie im sozialen und politischen Kontext der Basler Geschichte des 19. Jahrhunderts - Kriemler, Daniel (LIBRUM Publishers & Editors LLC, 2016)
The members of the 19th century Basel Reading Society belonged to the socio-cultural bourgeoisie. This study is a biography of this group of members of civil society: its transformation is observed and interpreted against the backdrop of the club history of the Reading Society and within the local historical context. The collective body is analysed and portrayed with respect to both the imposed statutory framework, quantitative development, social, political and historical economic factors, and also to individual biographical data.